Safety and immunogenicity of a paediatric presentation of an influenza vaccine. Issue 6 (1st December 2000) - Gonzalez, M; Pirez, M C; Ward, E; Dibarboure, H; García, A; Picolet, H
Abstract : BACKGROUND: Flu vaccination in otherwise healthy infants and young children is important to prevent severe disease, as well as to control epidemic spread of influenza infection. AIMS: To examine the safety and immunogenicity of a paediatric presentation of a purified, inactivated, triton split influenza vaccine. METHODS: Two doses of the vaccine, provided in prefilled syringes of 0.25 ml, were administered, one month apart, to 67 children under 3 years of age. RESULTS: Nine cases of immediate reaction to vaccination (macules/papules) were observed after the second injection only. During the study period, 9% of children experienced at least one delayed local reaction, and 28% of children presented at least one systemic reaction. Almost all reactions were mild and transient. Immunogenicity results surpassed the European Community recommendations for a 0.50 ml dose of vaccine in adults. CONCLUSION: This paediatric formulation of inactivated flu vaccine appears safe and immunogenic in children from 6 months to 3 years of age; the convenient presentation in a prefilled syringe of 0.25 ml volume will facilitate administration of the dose recommended for young children.